Perception of Direction of Moving Sounds ―Study on Adaptive Method - Kudo, Akihiro; Takizawa, Tetsu; Takei, Amane (Transaction of the Japan Society for Simulation Technology, 2022)
In this study, we attempted to clarify the MAMA of broadband noise in virtual space. In the previous studies, MAMA has been measured by the method of constant stimuli. However, The results should not be taken as an estimate of the average human MAMA due to the inappropriate fitting method. Therefore, we re-examined the MAMA by QUEST+ method. In the psychophysical experiment, the subject was asked to answer the direction of movement of a circularly moving sound image at an equidistant distance of 1.5 m from the subject on a horizontal plane, using VR sound with headphones. The moving speed was at 8[deg/sec]. 9 subjects participated in this experiment, and the average MAMA were 3[deg] at 0[deg], 14[deg] at 45[deg], and 36[deg] at 90[deg]. These results indicate that the MAMA of broadband noise is larger in virtual space than in real space, and the manner of its increase was linear. By the results of the QUEST+ method, it was concluded that measurement accuracy is almost the same. And the measurement efficiency was higher than the method of constant stimuli since there are fewer procedures to calculate confidence intervals.